دراسة تحليلية واستشرافية لإنتاج الحبوب في الجزائر للفترة (1970-2020) - سلامـي, أحمـد (Recherches économiques et managériales; Vol. 12 No 01 (2018): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(Décembre), 2020)
نهدف من هذه الدراسة، إلى رصد وتحليل الحالة الراهنة للإنتاج المحلي من الحبوب، فضلا عن صياغة نموذج قياسي لانتاج الحبوب وتقديم رؤية مستقبلية واستشرافية باتجاهاته في آفاق 2020، وذلك باستخدام منهجية "بوكس-جينكينز" للتنبؤ. نتائج الدراسة تشير إلى أن الإنتاج المحلي للحبوب لا يزال قاصرا على تلبية الطلب المحلي المتزايد، وأن هذا الإنتاج لن يتجاوز في أحسن أحواله حاجز 6.33 مليون طن في آفاق 2020، في مقابل احتياجات تفوق 8 مليون طن، إذا ما تواصل نمو الإنتاج على نفس الوتيرة التي يتبعها حاليا. من هنا فإنه يمكن تصور المشكلة الغذائية التي ستحدث، وما يتبع ذلك من أعباء اقتصادية وسياسية، خاصة إذا ما صاحب ذلك ندرة في العملات الأجنبية اللازمة للاستيراد، ذلك أن أسعار النفط تعرف حاليا هبوطا حادا وعدم استقرار. لذا أوصت الدراسة بأن تسعى الدولة إلى إعادة الاعتبار للقطاع الزراعي ضمن السياسة الاقتصادية، ومنح الأولوية لتحسين وتكثيف إنتاج الحبوب، ذلك أنه المدخل الصحيح لتفادي مخاطر التبعية الغذائية للخارج. الكلمات المفتاحية : تنبؤ ؛ انتاج حبوب ؛ منهجية بوكس جينكنز ؛ اكتفاء ذاتي ؛ تبعية غذائية. Abstract :                 This study aims to monitor and analyze the current state of domestic cereal production, as well as to formulate of an econometric model for grain production and provide future projections for 2020 using the Box-Jenkins methodology. The results of the study indicate that domestic cereal production is still limited to meet growing domestic demand, and that this production will not exceed at best the 6.33 million tons limit in the 2020 prospects, compared to needs of more than 8 million tons, if production continues at the same pace as Follow them now. Hence, it is possible to imagine the food problem that will occur, and the consequent economic and political burdens, especially if accompanied by the scarcity of foreign exchange necessary for import, as oil prices are currently known as a sharp decline and instability. Therefore, the study recommended that the state seek to rehabilitate the agricultural sector within the economic policy, and give priority to improving and intensifying the production of grain, as it is the right way to avoid the risks of food dependency abroad.